Histological and Biochemical Effect of Galangin Conjugated Gold Nanoparticles on the kidneys Damage Induced by Carbon Tetrachloride of Adult Male Albino Mice - Abeed, Bassem Sultan; Al-Shmgani , Hanady Salim; Khalil, Khalil A. A.; Mohammed, Hamdoon A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This study aimed to determine histological and functional effects of Galangin (Gal) conjugated with Gold nanoparticles (AuNPs) on the Kidneys male albino mice treated with CCL4. Gold nanoparticles were prepared chemically by Turkevich Method. Characterizing of the prepared AuNPs and AuNPs+Gal was carried out using UV Spectrophotometry, X-Ray Diffraction (XRD) and particle size,. For the in vivo study, 42 adult male albino mice were used and randomly distributed into seven groups and experiment extended for 14 days, first group (G1) was control group without any treatment, (G2) group injected intra-peritoneal (i.p) with CCl4 once a week to the end of experiments, (G3) injected with AuNPs, (G4 and G5) were injected with Gal at 10 and 20 mg/kg concentration respectively, (G6 and G7) were injected with AuNPs-Gal 10 mg/kg and AuNPs+Gal 20mg/kg respectively. The results showed a spherical shape with average size at 61.6 nm, the absorption spectrum was 535 nm, and the crystalline nature of the conjugated solution using XRD was confirmed, where the spectrum appears at 45.4, 38, 32 and 24 C°. In vivo study results recorded different histopathological alteration in the kidney tissue of mice treated with CCL4, and treatment with AuNPs+Gal significantly improved the histology architecture in a dose depended manner. Additionally, the levels of urea and creatinine in blood serum were much higher in the CCL4 group, and they were significantly reduced to normal levels after treatment with Cal and conjugated AuNPs+Gal. These findings revealed that galangin loaded on gold nanoparticles positively improved the damage induced by CCL4, providing a potentially effective natural treatment following extensive appropriate developments.